Effects of Surgery and Radiotherapy on Recurrent Skull Base Meningiomas: Clinical and Biological Analyses - Ichimura, Shinya; Kawase, Takeshi (Journal of Neurological Surgery Part B: Skull Base, 2019)
We reviewed the medical records of 392 patients who underwent initial surgery for skull base meningiomas between 1983 and 2008. Among them, 32 (8.2%) showed tumor recurrence. Risk factors for recurrence were analyzed clinically and biologically. Recurrent cases were treated with radiotherapy, surgery, or both. In reoperation cases, pathological and biological changes were analyzed and compared between groups with or without radiotherapy. The recurrence rate was statistically high in cases of partial tumor removal and in patients with tumor in the cavernous sinus, tumors with histological WHO (World Health Organization) grade ≥ II or MIB-1 index > 3. The local control rate of postoperative radiotherapy for recurrent cases was 66.7%. Malignant transformation and MIB-1 index elevation was observed more frequently in patients who underwent reoperation after radiotherapy than in the reoperation-only group. Risk factors for recurrence of skull base meningiomas are as follows: (1) partial tumor removal, (2) tumor in the cavernous sinus, (3) histological WHO grade ≥ II, or (4) MIB-1 index > 3. Postoperative radiotherapy might be effective for tumor recurrence. However, the indications for radiotherapy should be carefully considered because postsurgical radiotherapy may increase biological activity, inducing malignant transformation.
Keywords: malignant transformation; MIB-1 index; radiotherapy; recurrence; skull base meningiomas; surgery